Field and model assessments of irrigated soybean responses to increased air temperature. (28th September 2020) - Sima, M. W.; Fang, Q. X.; Burkey, K. O.; Ray, S. J.; Pursley, W. A.; Kersebaum, K. C.; Boote, K. J.; Malone, R. W.
Abstract: Correctly quantifying elevated air temperature effects on crop yield through field experiments and crop modeling is essential for developing adaptation strategies under climate change. In this study, the effects of elevated air temperature on soybean [ Glycine max (L.) Merr.] production were investigated using a four‐year open top chamber experiment (2015–2018) in North Carolina, USA. The experimental results showed that an increase of average air temperature during growing seasons by 3.4 °C to 25.7 °C decreased seed yield by 22%, final biomass by 11%, and harvest index by 12%, but did not significantly affect maturity date. The reduction in seed yield was more associated with reduction in seed number (19%) than in seed weight (2%). Two soybean growth models (CROPGRO and HERMES) in the Root Zone Water Quality Model (RZWQM) were evaluated against measured temperature responses from the four‐year experiment. Both crop models simulated lower reduction in seed yield (15% for CROPGRO and 17% for HERMES), but simulated reduction in biomass was lower by CROPGRO (7%) and higher by HERMES (20%) than that measured in the chambers. Between the two models, HERMES predicted slightly better responses of seed yield and biomass to temperature across the four years than CROPGRO, whereas the opposite was true for maturity date and harvest index. However, HERMES simulated earlier maturity dates for heated treatment than observed, suggesting that improvements are needed in the model for soybean phenology response to temperature increase.